Distribution and Relative Abundance of Bean Leaf Beetles (Ootheca spp.) (Insecta: Coleoptera: Chrysomelidae) in Uganda - Charles Halerimana (MDPI AG, 2021)
Bean leaf beetles (Ootheca spp.) (Insecta: Coleoptera: Chrysomelidae) are one of Africa’s most destructive pests of common bean and other leguminous crops. The beetles are widely distributed in Africa where they are estimated to cause annual crop yield losses of 116,400 tons of crop yields in sub-Saharan Africa. Despite their importance, little is known about the distribution, relative abundance and damage caused by bean leaf beetles in Uganda. As a result, the development of effective management methods has been hampered. We conducted surveys in six key Ugandan agro-ecological zones to determine the species distribution and relative abundance of bean leaf beetles. Findings indicate that leaf beetles belonging to 12 genera are present, including members of the genera Afrophthalma Medvedev, 1980, Buphonella Jacoby, 1903, Chrysochrus Chevrolat in Dejean, 1836, Diacantha Dejean, 1845, Exosoma Jacoby, 1903, Lamprocopa Hincks, 1949, Lema Fabricius, 1798, Nisotra Baly, 1864, Neobarombiella Bolz and Wagner, 2012, Ootheca Dejean, 1935, Parasbecesta Laboissière, 1940, and Plagiodera Dejean, 1835. We identified only three species belonging to the genus Ootheca: O. mutabilis, O. proteus, and O. orientalis. Seventy percent of all the beetles collected were O. mutabilis and these were present in all agro-ecological zones studied. The Northern Moist Farmlands (21.9%), West Nile Farmlands (12.9%), Central Wooded Savanna (4.4%) and Southern and Eastern Lake Kyoga Basin (1.4%) were the only agro-ecological zones where O. proteus was found. Only one specimen of O. orientalis was found at a single site in the Central Wooded Savanna. The Northern Moist Farmlands had a significantly (p < 0.05) higher bean leaf beetle density than the West Nile Farmlands and Southwestern Highlands. Similarly, the Northern Moist Farmlands had the highest beetle foliar damage per plant (1.15 ± 0.05), while the Southwestern Highlands had the lowest (0.03 ± 0.02). We provide the first information on Ootheca species distribution, abundance and damage in Uganda. Our findings provide a foundation for assessing the importance of Ootheca spp. as common bean pests in Uganda.